The Effect of Nuhonni-Tulaar Rheumatic Exercise on Pain Reduction of Knee Osteoarthritis Patients - Ferius Soewito; Siti Annisa Nuhonni; Elida Ilyas; Muchtaruddin Mansyur; Angela BM Tulaar (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: Knee osteoarthritis patient has the risk for ambulation disability as a result of knee pain. Nuhonni-Tulaar rheumatic exercise was designed to prevent complications of rheumatic diseasesincluding knee osteoarthritis. The purpose of this study is to investigate the effectivity of Nuhonni-Tulaar rheumatic exercise to reduce pain of knee osteoarthritis patient.Methods: Twenty two subjects did the rheumatic exercise thrice a week in the gymnasium of medicalrehabilitation department Cipto Mangunkusumo hospital. Twenty other subjects, the control group, didthe standard hamstring stretching exercise at home. Each group performed the exercise for 8 weeks.Pain was measured using Visual Analog Scale (VAS) each week and analyzed before and after theintervention.Results: After 8 weeks VAS was reduced 1.5 in the intervention group while in the control group the reduction was 0.9. VAS was then transformed into no pain, mild pain, moderate pain and severepain. VAS was significantly reduced in the intervention group (p=0.002) but not in the control group (p=0.059). VAS changes between the two groups was significantly different (p=0.004).Conclusions: Rheumatic exercise has greater benefit in reducing pain than standard stretching exercise.Warming up, core exercise II and cooling down is safe and comfortable for knee osteoarthritis patientwith grade I-II Kellgren Lawrence radiographic grading.Keywords: Nuhonni-Tulaar Rheumatic exercise, Knee osteoarthritis, Visual Analog Scale